Pyrene–benzothiadiazole‐based copolymers for application in photovoltaic devices. (22nd July 2016) - Alqurashy, Bakhet A.; Cartwright, Luke; Iraqi, Ahmed; Zhang, Yiwei; Lidzey, David G.
Abstract : The preparation and characterization of four narrow band gap pyrene–benzothiadiazole‐based alternating copolymers are presented. An investigation of the impact of attaching different solubilizing groups to the pyrene repeat units on the optical, electrochemical, and thermal properties of the resulting materials was undertaken along with studies on the aggregation of polymer chains in the solid state. Unsurprisingly, polymers which had the smaller 2‐ethylhexyl chains attached to the pyrene units (PPEH ‐DTBT and PPEH ‐DTffBT) displayed lower molecular weights relative to polymers with larger 2‐hexyldecyl substituents (PPHD ‐DTBT and PPHD ‐DTffBT). Despite this, the 2‐ethylhexyl substituted polymers displayed narrower optical band gaps relative to their analogous 2‐hexyldecyl substituted polymers. Of all polymers synthesized, PPEH ‐DTBT displayed the lowest optical band gap (1.76 eV) in the series. All polymers display degradation temperatures in excess of 300°C. Polymers with smaller alkyl chains on the pyrene units display shallower highest occupied molecular orbital levels, which could be due to increased intramolecular charge transfer between the donor and acceptor units. Preliminary investigations on bulk heterojunction solar cells with a device structure indium tin oxide/poly(3, 4‐ethylenedioxythiophene) : polystyrene sulfonate /Polymer : PC70 BM/Ca/Al were undertaken. Polymer/PC70 BM blend ratios of one third were used in these studies and have indicated that PPEH ‐DTBT displayed the highest efficiency with a power conversion efficiency of 1.86%. Copyright © 2016 John Wiley & Sons, Ltd.